Trapeze - Mawer, Simon 1948- (Other Press, 2012)
At the age of 19, fluent-French-speaking Briton Marian Sutro is recruited for service in the Special Operations Executive during World War II, only to find that another secret organization wants her to infiltrate Paris to persuade a research physicist to join the Allied war effort
Keywords: Young women / Fiction; World War, 1939-1945 / Underground movements / Fiction; Geschichte; Weltkrieg (1939-1945); France / History / German occupation, 1940-1945 / Fiction; Frankreich